Caracterización de las pérdidas de propagación en el canal de radio V2V para un escenario suburbano - Herman Antonio Fernández González; Lorenzo Rubio Arjona; Vicent Miguel Rodrigo Peñarroca; Juan Ribera Reig Pascual (Tecnura, 2013)
The design of future vehicular communication systems is receiving considerable attention from the scientific community and also from standard organizations and vehicle manufacturers due to the introduction of intelligent transportation systems (ITS). These concepts bring potential applications for improving traveling conditions in terms of road safety, aiming at reducing the number of traffic accidents as well as providing easy traffic flow. Moreover; in order to design, evaluate and optimize ITS applications oriented towards vehicular safety and based on wireless systems; knowledge of the propagation channel is vital, in particular path-loss conditions. In this context, this paper analyzes path loss in terms of transmitter (Tx) and receiver (Rx) separation distance. The analysis is based on experimental channel measurements carried out at 700 MHz and 5,9 GHz. Values for the path loss exponent and the standard deviation of shadowing are reported and compared with other results published in the literature. The measurement campaign was conducted in a suburban area characterized by high-traffic density.